Alternatif Perencanaan Terowongan Pengelak (Diversion Tunnel) Bendungan Pamukkulu - Natalia Anga; Melly Lukman; Erni Rante Bungin (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
In the construction of the Pamukkulu Dam, the initial design used in planning the evasion tunnel was a horseshoe shape. However, in this study an alternative planning in the form of a circle is proposed.The regional average rainfall was calculated by the Thiessen Polygon method and the design rainfall analysis calculation with a return period of 2,5,10,25 years using the Gumbel method, Log Normal method, and Pearson Type III Log method. By using the distribution suitability test Smirnov-Kolmogorov Test and Chi- Square Test. The design discharge was analyzed using the Nakayasu. Synthesis Unit Hydrograph method.Based on the results of this study, the 25-year design flood discharge was 291.548 m3/second and the circular escape tunnel design was 6 m in diameter with an energy loss height of 11.821 m and the design height of the cofferdam crest was +85.571 m.